Single-Stage Repair of Coarctation of the Aorta and Ventricular Septal Defect: A Comparison of Surgical Strategies and Resource Utilization. (September 2017) - Callahan, Connor; Saudek, David; Shillingford, Amanda; Creighton, Sara; Hill, Garick; Johnson, William; Tweddell, James S.; Mitchell, Michael E.; Woods, Ronald K.
Background: We sought to compare clinical outcomes and resource utilization for two surgical approaches for single-stage repair of coarctation of the aorta and ventricular septal defect (VSD). Methods: This was a retrospective chart review of 21 consecutive neonates and infants undergoing single-stage repair of coarctation of the aorta and VSD. Group 1 included 13 patients with both arch repair and VSD repair completed via sternotomy. Group 2 included eight patients with off-pump arch repair via left thoracotomy followed by repositioning and VSD repair via sternotomy. Primary clinical outcome was arch reintervention. Secondary outcomes included various measures of resource utilization. Results: Group 1 patients demonstrated younger age at repair (median of 10 days vs 57 days for group 2; P = .05) and lower proximal arch z scores (−4.2 vs −2.3 for group 2; P = .003). Arch reintervention occurred in 0 of 8 patients in group 2 and 1 (7.7%) of 13 patients in group 1 ( P = nonsignificant). Group 2 was associated with lower total charges (US$68, 301 vs US$211, 723 for group 1; P = .0007), shorter length of stay (8 days vs 23 days for group 1; P = .004), and shorter duration of postoperative mechanical ventilation (0.5 days vs 4.0 days for group 1; P = .0008). Group 2 was also associated with shorter total cardiopulmonary bypass time (86 minutes vs 201 minutes for group 1; P = .0009). Conclusion: Single-stage two-incision repair of coarctation and VSD in appropriately selected patients may be associated with higher value of care. Confirmation of this finding will require further study based on larger numbers of patients.